(untitled) (Journal of the College of Basic Education, 2023)
Poetic, of which more than ninety witnesses are not known to say, and more than eighty witnesses are different in their attribution to saying their own eyes, so we have - as Dr. Fadel said - more than seventy and one hundred witnesses of which the real saying is not known (1).There is no doubt that this issue calls for a pause of contemplation. That in the books of grammar - on its diversity - is a relatively few of the unknown poetic evidences that are a common matter since the time of the first grammatical author who prayed to us and it is the book of Sibuh (180) Of the attributed verses, fifty verses are not known to say. As for the number of these evidences increasing to reach nearly half the number of evidences in a numbered grammar book in the Ummahs, it is necessary to know its circumstances and circumstances that led to it.